Social cognition functions in persons with epilepsia - G. Jasionytė; A. Jasionis; R. Mameniškienė (Neurologijos seminarai)
This review article aims to present and provide concise information on the social cognitive functions in people with epilepsy. Social cognition is one of the six major cognitive domains, according to DSM-V, and is crucial for interpersonal communication. Major subdomains of this domain are recognition of emotions and theory of mind (understanding of mental states (emotions, beliefs, intentions and desires) of other people). Deficits of social cognition in epilepsy have been described by various researchers and are thought to be independently related with worse quality of life of people with epilepsy. We introduce the main social cognitive functions – recognition of emotions and theory of mind, their development and commonly used cognitive tasks to evaluate them. Further we provide summarized information on the deficits in social cognition in epilepsy and discuss main demographic and clinical correlates. Last paragraphs are concerned with special features of social cognition in major types of adult epilepsy and possible future interventions.